(untitled) (Світ фінансів, 2017)
Іванова А. М. Особливості здійснення фіскальної децентралізації в Україні. Виявлено важливу роль місцевих бюджетів у формуванні Зведеного бюджету України. Розраховано значення показника фінансової децентралізації. Проведено аналіз складу та структури дохідної частини місцевих бюджетів. Здійснено оцінку динаміки власних податкових надходжень місцевих бюджетів. Розглянуто зміни до Бюджетного кодексу України в частині перерозподілу податкових надходжень між державним і місцевими бюджетами. Доведено, що низька частка доходів місцевих бюджетів та неефективний розподіл їхніх видатків ускладнюють процес реалізації фіскальної децентралізації. Иванова А. Н. Особенности осуществления фискальной децентрализации в Украине. Определена важная роль местных бюджетов в формировании Сводного бюджета Украины. Рассчитано значение показателя финансовой децентрализации. Проанализированы состав и структура доходной части местных бюджетов. Проведена оценка динамики собственных налоговых поступлений местных бюджетов. Рассмотрены изменения Бюджетного кодекса Украины, касающиеся перераспределения налоговых поступлений между государственным и местными бюджетами. Доказано, что низкая доля доходов местных бюджетов и неэффективное распределение их расходов усложняют процесс реализации фискальной децентрализации. Ivanova A. Especially the implementation of fiscal decentralization in Ukraine. Introduction. The process of decentralization has had a considerable influence on the formation of the budget system of Ukraine by providing the sub-national governments with the fiscal authority. However, Ukraine does not yet have a firmly established decentralized model of relationships between the levels of authority that would contribute to the country’s economic growth. Purpose. The aim of the present article is to study the role of the fiscal decentralization in establishing the budget system of Ukraine. Results. Thus, the role of the local budgets in shaping the general budget of Ukraine has been researched. The index of the financial decentralization has been calculated. It has been found that this index decreased from 32,6% in 2011 to 29,8% in 2015. The analysis of the composition and structure of the income share of local budgets has been made. As a result, it has been found that the biggest share of local budget income is that from taxes (33%) and official transfers (59%). It has been further established that 72% of the tax component of the local budget income is formed due to the income assigned to the local budget rather than the local authority’s own income. Furthermore, the composition and structure of the tax of local budgets has been analysed. As a consequence, it has been established that the single tax (41%) is the most important one among the local taxes. The role of inter-budgetary transfers in the process of balancing the local budgets has been researched. The amendments made to the Budget Code of Ukraine in the part concerning the distribution of official transfers between the state and local budgets have been studied. The composition and structure of the expenditure of the local budgets has been analyzed. Thus, it has been found that approximately 90% of all the expenditure is the regular expenditure – i.e. social expenditure. Capital expenses directed at building infrastructure of a particular territory are only around 10%. Such a disproportion leads to spending costs without any further positive economic development. The low share of income to the local budgets and the ineffective distribution of their expenditure result in unfavorable conditions for fiscal decentralization. Conclusion. As a result, for the budgetary system of Ukraine to function effectively, a more systematic approach is required to the process of fiscal decentralization. Thus, an accurate division between the functional authorities of different levels of the budgetary system should be conducted.